2011
DOI: 10.1002/joc.2199
|View full text |Cite
|
Sign up to set email alerts
|

Meteorological characteristics and potential causes of the 2007 flood in sub‐Saharan Africa

Abstract: ABSTRACT:In August and September 2007 media and aid organizations reported on a severe flood in large parts of sub-Saharan Africa caused by a sequence of extreme rain events. However, the reporting was partly controversial and much was speculated about how unusual the flood event was. Here, we analyse various observational data sets in order to assess and to compare the spatio-temporal characteristics and intensity of the flood and the associated rain events. The return times are estimated from daily precipita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
75
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(81 citation statements)
references
References 56 publications
(86 reference statements)
4
75
0
Order By: Relevance
“…This increase in flood related fatalities and economic losses may be due to an increase in inundations, but also potentially to an increase in exposure and vulnerability, as suggested by Aich et al (2016) [38]. The results of Paeth et al [39] and Lafore et al [40] also suggest that many factors, from synoptic-scale to large-scale circulations, including regional features and teleconnection patterns, contribute to the extremeness of the rainfall events that lead to flooding.…”
Section: Principal Component Analysis (Pca)mentioning
confidence: 95%
See 2 more Smart Citations
“…This increase in flood related fatalities and economic losses may be due to an increase in inundations, but also potentially to an increase in exposure and vulnerability, as suggested by Aich et al (2016) [38]. The results of Paeth et al [39] and Lafore et al [40] also suggest that many factors, from synoptic-scale to large-scale circulations, including regional features and teleconnection patterns, contribute to the extremeness of the rainfall events that lead to flooding.…”
Section: Principal Component Analysis (Pca)mentioning
confidence: 95%
“…In sharp spatial scale contrast, large areas from four countries (the southern part of Burkina Faso, the northern parts of Benin, Togo and Ghana) provided stream flows to tributaries of the Volta River in August and September 2007 during a flood event that was part of a very active monsoon. Paeth et al [39] suggested that remote influences of anomalously high Atlantic SST (Sea Surface Temperature) and of a La Niña event in the Tropical Pacific played a role in this event. However, it is notable that the extreme rainfall event that occurred at Ouagadougou in 2009 was associated with very distinct large-scale and regional patterns [40].…”
Section: As a Conclusion The Temporal Evolution Of The Sudanian Hydrmentioning
confidence: 99%
See 1 more Smart Citation
“…e selection of the GPCC data as reference data for this evaluation study is based on the fact that they have been applied in similar model evaluation studies (e.g., [31,32]) over the West African region. Other studies including Gruber et al [39], Nicholson et al [37], Paeth et al [38], and Nikulin et al [29] have demonstrated the robustness of GPCC data in reproducing observed precipitation in the West African region. ese studies expressed confidence in this particular data set.…”
Section: Datamentioning
confidence: 92%
“…Due to the highly varying spatial distribution of precipitation, spatial density of observed precipitation data is crucial over West Africa. Studies (e.g., [37,38]) have indicated that the availability of high-quality data set especially in the case of precipitation over West Africa is problematic. Consequently, gridded observational open-source data sets become the practical option for model validation purposes within the region.…”
Section: Datamentioning
confidence: 99%